Sulphamethazine in poultry manure changes carbon and nitrogen mineralisation in soils. Issue 10 (25th November 2016) - Awad, Yasser M.; Ok, Yong Sik; Igalavithana, Avanthi Deshani; Lee, Young Han; Sonn, Yeon-Kyu; Usman, Adel R. A.; Al-Wabel, Mohammad I.; Lee, Sang Soo
ABSTRACT: Antibiotics are newly emerging organic pollutants in manure, soil, vegetables and water. Animal manure application might be leading to the accumulation of antibiotics in the farmland. However, the effect of sulphamethazine (SMZ) on the soil microbial community was scarcely investigated. This study was aimed to evaluate the impact of SMZ on poultry manure, on the structure and function of microbial community, carbon mineralisation, and changes in nitrogen forms in soil via an incubation experiment lasting 56 d. The treatments consisted of poultry manure at 1% wt (PM), PM containing 20 mg kg −1 SMZ (PM + 20SMZ) and PM containing 100 mg kg −1 SMZ (PM + 100SMZ), along with the untreated soil (control). Solid phase extraction was performed to measure the SMZ concentration in soils using high-pressure liquid chromatography. The cumulative CO2 -C was increased in all treated soils over the incubation period compared to the control. The PM + 100SMZ had the highest increase in cumulative CO2 -C from the soil at 56 d of incubation. The treatment of PM + 20SMZ showed a short-term decrease in nitrification rate in the soils at 1 d by altering the microbial community composition with 17% dissimilarity and decreasing the abundance of bacteria compared to PM-treated soil. The PM + 100SMZ increased C mineralisation in the soil.